FORMATION OF STUDENTS' LEADERSHIP QUALITIES THROUGH PHYSICAL EDUCATION (Physical Culture and Sport: Scientific Perspective, 2025)
The article explores the impact of physical education on the formation of students' leadership qualities. It substantiates that physical culture is a key factor in personality development, as it fosters initiative, responsibility, endurance, and the ability to communicate effectively. The research emphasizes that the process of physical education creates favorable conditions for the development of organizational abilities, decision-making skills in non-standard situations, and effective teamwork. Modern approaches to physical education in higher education institutions are examined, focusing on their role in stimulating students' leadership potential. Special attention is paid to the importance of team sports, competitive activities, and psychological resilience training. Various methods that contribute to leadership development are analyzed, including the individualization of physical activity, the promotion of self-control and willpower, and the encouragement of independent decision-making during training sessions and competitive events. It is proven that the implementation of innovative and effective physical education methodologies positively influences students' harmonious personal growth, enhances their physical and psycho-emotional preparedness, and strengthens their ability to take initiative and lead others. The study concludes that leadership development through physical culture is achievable with systematic training, the creation of an appropriate educational environment, and targeted pedagogical influence. Ensuring continuous engagement in physical activities and fostering an atmosphere of support and motivation are essential for maximizing students' leadership potential.Particular attention is paid to the importance of integrating physical education with other educational disciplines for the comprehensive development of students' leadership competencies, in particular through interdisciplinary approaches that combine physical activity with the development of cognitive, emotional, and social skills.
Keywords: physical education; leadership qualities; student youth; higher education institutions; physical culture; personal development